La metacognición como estrategia para detectar procesos cognitivos en niños con retraso mental - Ana Patricia Vázquez-Chaves; María Suzanne León-Rodríguez; María Judith Rodríguez-Ramírez (Universidad Nacional, Costa Rica, 2006)
Abstract. It was planned to detect the cognitive processes that mentally retarded children used when solving math problems, through the use or metacognitive strategies. The work was done whit a sample of twenty mentally retarded children that attend integrated classrooms from de provinces of Heredia and Alajuela. An instrument called Batería de Resolución de Situaciones Matemáticas (BARSIMAR) was used to detect the cognitive processes that children used when working with metacognitive strategies. The results show that the more cognitive engaged the children are, the more difficulty they will have when using cognitive processes to register the information in the short term memory. The advanced kids could use the processes in a better way, but with interferences and difficulty to recover the information form the long term memory and give correct answers to the cognitive task they are working on.